Nr2f1b control venous specification and angiogenic patterning during zebrafish vascular development. Issue 1 (December 2015) - Li, Ru-Fang; Wu, Ting-Yun; Mou, Yu-Zheng; Wang, Yi-Shan; Chen, Chun-Lin; Wu, Chang-Yi
Abstract Background The specification of vein and the patterning of intersegmental vessels (ISV) controlled by transcription factor is not fully characterized. The orphan nuclear receptor Chicken ovalbumin upstream promoter transcription factor II (CoupTFII, a.k.a NR2F2) positively regulates vein identity in mice. In this study, we show thatnr2f1b is important for vein and tip cell identity during zebrafish development. Results Nr2f1b mRNA is expressed in ventral lateral mesoderm at 15S stage and in vessels at 24 hpf consistent with a role in early vascular specification. Morpholino knockdown ofnr2f1b results in a decrease in both vein cell number and expression of the vein specific markerflt4 andmrc1, suggested its role in venous specification. We also show loss ofnr2f1b reduced ISV cell number and impairs ISV growth, which is likely due to the impairment of angiogenic cells migration and/or proliferation by time-lapse imaging. Consequently, nr2f1b morphants showed pericardial edema and circulation defects. Overexpression ofnr2f1b under the fli promoter increases the number of venous cells and ISV endothelial cells indicated the function ofnr2f1b is required and necessary for vascular development. We further showed thatnr2f1b likely interact withNotch signalling.nr2f1b expression is increased inrbpsuh morphants and DAPT-treatment embryos suggestednr2f1b is negatively regulated by Notch activity. Conclusions We shownr2f1b control venous specification and angiogenic patterning during zebrafish vascular development, which is mediated by Notch signalings.